CHANGING DIMENSION OF EDUCATION – A CRITICAL APPRAISAL OF NATIONAL EDUCATION POLICY – 2020 (International Journal of Food and Nutritional Sciences, 2023)
While NEP 2020 aims for many much-needed positive changes, the backdoor passing of the bill and the possibility of amplifying existing fault lines in Indian society needs to be looked into. The policy will seemingly increase the economic divide in a country that is already divided by religion, caste, gender, and wealth. It makes it nearly impossible for disadvantaged classes to climb up the social ladder. The NEP supposedly envisages decolonizing young Indian mind; however, in reality could that translate to the saffronisation of education? Earlier this year crucial topics for students, such as democratic rights, challenges to democracy, citizenship, food security, gender, religion, caste, and secularism were dropped from the syllabus. Are all of these moves stepping stones to achieve saffronisation? In this scenario holistic, interdisciplinary, multidisciplinary, overall learning could possibly be a front to cover all the above aspects. It will take years before the policy goes into full swing and only then will these complexities become apparent. The method of implementation will determine its successes and failures. The flaws in this policy need to be addressed with deliberation through proper code of conduct to reduce the current shortfalls. The Committee working on the policy has succinctly identified the role of higher education as ‘promoting human as well as societal wellbeing and developing India as envisioned in its Constitution—a democratic, just, socially conscious, cultured and humane nation, upholding liberty, equality, fraternity, and justice for all.’